2022
DOI: 10.18235/0004459
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Cities: Healthy Cities for All

Abstract: Inter-American Development Bank Felipe Herrera Library Inclusive cities: healthy cities for all / edited by Nora Libertun. p. cm. -(IDB Monograph ; 984) Includes bibliographic references. 1. Environmental health-Latin America. 2. Housing and health-Latin America. 3. Health risk assessment-Latin America. 4. Urban policy-Latin America. I. Libertun, Nora. II.Inter-American Development Bank. Housing and Urban Development Division. III. Series. IDB-MG-984This publication reports on some of the health challenges fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 321 publications
(396 reference statements)
0
0
0
Order By: Relevance
“…Another, by Michaels et al (2021), argued that, compared to untreated neighboring areas, improved informal neighborhoods in Dar es Salaam, Tanzania, either showed no significant improvement or became even worse after a period of two to three decades. Finally, Libertun de Duren et al (2022) found the condition of the infrastructure in upgraded favelas in Rio de Janeiro no better after a decade than that in the favelas that were not upgraded.…”
Section: The Supply Of Formal Versus Informal Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another, by Michaels et al (2021), argued that, compared to untreated neighboring areas, improved informal neighborhoods in Dar es Salaam, Tanzania, either showed no significant improvement or became even worse after a period of two to three decades. Finally, Libertun de Duren et al (2022) found the condition of the infrastructure in upgraded favelas in Rio de Janeiro no better after a decade than that in the favelas that were not upgraded.…”
Section: The Supply Of Formal Versus Informal Housingmentioning
confidence: 99%
“…Even after controlling for key variables, the life expectancy of women living in the neighborhoods of Santiago de Chile in the lowest income decile is 18 years less than for those living in neighborhoods in the top decile. Significantly lower life expectancy has also been documented for poorer areas of Panama City, Mexico City, Buenos Aires, and Belo Horizonte, Brazil (Libertun de Duren et al 2022) In terms of access to adequate housing in both formal and informal markets in the region, the most current comparable data show that housing deficits affect 55 million households, or about 45 percent of the total population (Bouillon 2012). a The incidence varies by country, with less than 15 percent of the population affected in Chile and Costa Rica and more than 55 percent in Bolivia.…”
Section: Boosting Housing Supplymentioning
confidence: 99%
“…La planificación urbana desempeña un papel crítico en la promoción de la salud y el bienestar de las comunidades, ya que las políticas urbanas determinan el aire que respiramos, la calidad de los espacios públicos, la manera de desplazarnos y el acceso a servicios (12,(15)(16)(17). Dependiendo de las decisiones de los planeadores urbanos, las acciones públicas pueden tanto contribuir a mejorar los resultados en salud como ir en detrimento de estos (12).…”
unclassified